IMPLEMENTASI MEDIA AUDIO DALAM KEGIATAN PROGRAM TAHFIZH AL-QUR’AN DI SMPN 3 KINALI - Fauziah; Darul Ilmi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2023)
Abstrak. This research was motivated by the fact that throughout the implementation of the tahfizh al-Qur'an program activities at SMPN 3 Kinali which were carried out on Wednesdays by memorizing surah al-Baqarah at 11.00-12.00 and on Saturdays the students were focused on memorizing the chapter. 30 at 07.30-09.00. In the application of using audio media in the Vlll 3 category, it has not worked as it should, as evidenced by students having difficulty remembering the Qur'an due to lack of interest and lack of focus in remembering the Qur'an regarding This was observed at least by students who submitted mahfuz al-Qur'an, aspects of the area and media such as cellphones that did not support which had a negative impact on students due to students' mistakes in using them. The method used is a qualitative descriptive approach. Methods for collecting monitoring information, questions and answers, and elections. The key information is the tahfizh al-Qur'an teacher. Based on the findings of studies conducted by observers, the results in implementing the Al-Qur'an tahfizh program with the exploitation of audio media in the Vlll 3 category have not been encouraging because there are still students who have not reached the expected targets.